INFORMATION SUPPORT AS A FACTOR OF IMPROVING INVESTMENT ATTRACTIVENESS AND GROWTH OF SOCIAL RESPONSIBILITY - Vladislav A. Romanchenko (Статистика и экономика)
Nowadays there is a need in information support in contemporary economy. This provides useful interactions between government and society. The emphasis should be made on an activity of government because of its authority in applying social and economic policies. Therefore developing of e-resources providing information to all members interested in it (such as investors and researchers) could lead to an elimination of transaction costs. The article examines the problem of information openness of clusters developing by The Ministry of Economic Development and Trade in Russian Federation.